2010
DOI: 10.1155/2010/460607
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junctions: A Barrier to the Initiation and Progression of Breast Cancer?

Abstract: Breast cancer is a complex and heterogeneous disease that arises from epithelial cells lining the breast ducts and lobules. Correct adhesion between adjacent epithelial cells is important in determining the normal structure and function of epithelial tissues, and there is accumulating evidence that dysregulated cell-cell adhesion is associated with many cancers. This review will focus on one cell-cell adhesion complex, the tight junction (TJ), and summarize recent evidence that TJs may participate in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 210 publications
(268 reference statements)
0
58
0
1
Order By: Relevance
“…The tight junctions consist of several components: integral membrane proteins, cytoplasmic proteins and cytoskeletal proteins (Brennan, et al, 2010). To date, a number of integral membrane proteins are associated with TJ, occludin, adhesion molecules, claudin family, etc., (Tsukita & Furuse 2000a, 2000b, Dhawan, et al, 2005Furuse, 2010).…”
Section: Claudinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tight junctions consist of several components: integral membrane proteins, cytoplasmic proteins and cytoskeletal proteins (Brennan, et al, 2010). To date, a number of integral membrane proteins are associated with TJ, occludin, adhesion molecules, claudin family, etc., (Tsukita & Furuse 2000a, 2000b, Dhawan, et al, 2005Furuse, 2010).…”
Section: Claudinsmentioning
confidence: 99%
“…Gradually has been shown that the molecular architecture of these complex is more numerous, the TJ is made up of at least 40 different components (Figure 1) (for review see: Schneeberger & Lynch, 2004; http://www.genome.jp/kegg/pathway/hsa/hsa04530.html). Among the elements that form part of integral membrane proteins, the claudin family (Clds; present active infinitive of claudeō, means close), has attracted the attention because of its relatively recent identification, the family includes 24 members in mammals (Furuse 2010, Brennan, et al, 2010, although Tsukita group recently has reported three new genes that code for Cldns 25, 26 and 27 (Mineta, et al, 2011). The Cldns were identified in 1998 by Dr. Tsukita in membrane fractions from chicken liver (enriched with TJ) through sucrose gradients.…”
Section: Claudinsmentioning
confidence: 99%
“…Cell-cell adhesion and the functional roles of JAMs in epithelial/endothelial cells 2.1 Introduction to cell-cell adhesion complexes and JAMs Cells within the breast tumour microenvironment physically interact with each other and with the extracellular matrix through a range of cell adhesion proteins. Cell adhesion proteins play fundamental roles in normal physiology (such as the control of cell polarity and epithelial barrier function), but their dysregulation has been shown to participate in tumour cell migration, invasion and adhesion (for review, see Brennan et al,2010). Adhesion proteins rarely exist in isolation from each other on the cell membrane, rather they form components of multi-cellular adhesion complexes containing a network of adhesion, scaffolding and signalling proteins.…”
Section: Cells Of the Breast Microenvironmentmentioning
confidence: 99%
“…Other factors such as resistance to apoptosis and ability to bypass senescence pathways also contribute significantly to the process [6]. Correct adhesion between adjacent epithelial cells is important in determining the normal structure and function of epithelial tissues [7]. Accumulating evidence suggests that dysregulated cell-cell adhesion is associated with development and progression of most epithelial cancers [8].…”
mentioning
confidence: 99%
“…The imbalance can also alter cell-cell and cell-extracellular matrix interactions, and cause disordered organ lining that makes cells chronically leaky to mitogens and growth factors. Together, these events can promote cancer formation in premalignant epithelial tissues [7]. Disruptive changes in TJ complex can also alter cell adhesion, free tumor cells from both neighboring cells and the underlying matrix; and confer onto them a migratory or invasive characteristics [20].…”
mentioning
confidence: 99%